PEMBERDAYAAN PELAYANAN PUBLIK MELALUI PENDEKATAN MALCOLM BALDRIGE NATIONAL QUALITY AWARD (MBNQA) - Sutarman, Sutarman (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2006)
The jargon ?public service? has become very popular. Despite the government?s efforts to improve public services through laws and regulations, people?s satisfaction toward public services is not evident yet. Hence, alternative approaches such as those from the private sector, need to be adopted and adapted in such a way so that they can be implemented within the public sector.